The Study of Drying Methods to Banana Flour Characteristic from Various Banana Variety - Edy Wibowo Kurniawan; Rudito; Muh Yamin (Jurnal Loupe, 2024)
Research conducted in Samarinda Agriculture State of Polytechnic and Plan Processing Laboratory of Agriculture Technology Faculty, Gadjah Mada University. This research aims to know the draining influence of physical chemistry characteristics of banana flour from various banana varieties as erudite information can be utilized further. Research carried out in two phases that are: first step represents the antecedent research for the most to find the compatible factors determining draining in yielding banana flour with the interesting color, and look for the direction operate banana draining of previous flour. This phase is done with sun drying of banana. Second step in the form of making banana flour from various banana varieties with the method which has been concluded at the first step. This phase is done by a water rate irrigation analysis, banana ripening level, and ranking test trough dryer machine. The results of research indicate that the draining which quickly trough dryer machine can produce the good banana flour, coveting the physical and also chemical characteristics of banana flour.